1987
DOI: 10.1182/blood.v70.4.1180.bloodjournal7041180
|View full text |Cite
|
Sign up to set email alerts
|

Chloramphenicol-induced bone marrow injury: possible role of bacterial metabolites of chloramphenicol

Abstract: To explore the potential role of some bacterial metabolites of chloramphenicol (CAP) in CAP-induced hematotoxicity, we examined their cytotoxic effects on bone marrow cells in vitro using a number of cytotoxicity parameters. Among the metabolites tested, dehydro-CAP (DHCAP) and p-nitrophenyl-2-amino-3 hydroxypropanone-HCI (NPAP) were more toxic than CAP. DHCAP was at least as toxic as nitroso-CAP. At concentrations of less than or equal to 10(-4) mol/L, DHCAP caused total irreversible inhibition of myeloid col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In addition, both act to inhibit protein synthesis at the ribosomal level. There is well-established evidence that reversible bone marrow suppression from chloramphenicol toxicity occurs from mitochondrial injury [4,5]. The chloramphenicol concept for myelosuppression proved to be an excellent framework to study new potential myelotoxins.…”
mentioning
confidence: 99%
“…In addition, both act to inhibit protein synthesis at the ribosomal level. There is well-established evidence that reversible bone marrow suppression from chloramphenicol toxicity occurs from mitochondrial injury [4,5]. The chloramphenicol concept for myelosuppression proved to be an excellent framework to study new potential myelotoxins.…”
mentioning
confidence: 99%
“…Notably, chloramphenicol (CAP) is the only other antimicrobial known to cause this degree of hematologic dyscrasia. 9 While the cause of aplastic anemia related to CAP is well described in the literature, the exact pathogenesis of metronidazole-induced hematologic dyscrasias is not well understood. Animal studies have revealed that metronidazole use results in fragmentation and breaks in the chromosomes of bone marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…The CONTAM Panel noted that these two papers reported a structure suggesting that HCl is covalently bound to the aminogroup of dehydro-CAP base. These metabolites have been implicated in the haematotoxicity of the antibiotic (Jimenez et al, 1987;Robbana-Barnat et al, 1997) and have been tested for their effects on DNA using the alkaline elution assay (Isildar et al, 1988b;Lafarge-Frayssinet et al, 1994) (see Section 7.2.7).…”
Section: Figurementioning
confidence: 99%
“…from tissue or gastro-enteric bacteria), are still a matter of debate or are simply not known. Compared with other metabolites, nitroso-chloramphenicol, dehydro-chloramphenicol and, to a lesser extent, dehydrochloramphenicol base and NPAP are characterised by higher cyto-and genotoxic potency (Lafarge-Fraissinet et al, 1994, Jimenez et al, 1987Isildar et al, 1988b;Robbana-Barnat et al, 1997). The presence of all such metabolites except dehydro-chloramphenicol base has been demonstrated in kidney, liver and muscle samples from broiler chickens orally administered 50 mg chloramphenicol/kg b.w.…”
Section: Potentially Toxic Metabolitesmentioning
confidence: 99%